Effect of Saccharomyces cerevisiae on the digestive health of the post-larvae of red tilapia Oreochromis sp - Pineda Santis, Hermes Rafael (2020)
The objective of this research was to evaluate the effect of Saccharomyses cerevisiae supplementation on digestive health and zootechnical parameters in postlarvae of red tilapia Oreochromis sp in the reversion phase, in a culture system with low water turnover, in San Jerónimo (Antioquia, Colombia). The trial was carried out for four weeks. Nine fiberglass channels (three repetitions) were used for a Control group (T1) and two probiotic treatments (T2: 16 g/kg feed = 16%) and (T3: 31 g/kg feed = 31%). The physicochemical characteristics of the water were analysed and zootechnical data were taken from the post-larva. Intestinal health was evaluated by histopathology. The results indicated that the physicochemical parameters of the water were similar between treatments and were within the acceptable range for the hybrid (average oxygen 9.1±0.4 mg/l, temperature 27.6±0.1 °C, constant pH = 8.9±0.4 and low turbidity). The survival percentage varied between 46.0±7.7 (T1) and 53.4±6.0% (T2), without significant differences between treatments. The increase in weight was 0.95±0.46, 0.71±0.26 and 1.32±0.58 g for the Control, T1 and T2, respectively (p<0.05) and the specific growth rate was 12.1±2.0, 11.4±1.4 and 13.3±1.7%/day for the Control, T1, and T2, respectively (p<0.05). Injuries were observed in the anterior intestine consistent with subacute villi necrosis, liver hepatocyte abnormality, and liver sinusoids due to glycogenic infiltration (T2).